Modificação da coloração de fundo da técnica de Ziehl-Neelsen Na identificação do Mycobacterium leprae - SIQUEIRA, Luiz Fernando de Góes (1982)
Authors analyse the counterstain with methylene blue solution in the usual Ziehl-Neelsen method. Considerations are made on the characteristics of the dye substance. A technique alteration is proposed: a "concomitant alkalization" of the classic aqueous methylene blue solution, by adding some drops of sodium hydroxide solution, 1:500, on the slide at the moment of the staining. By this tecnique it was observed: a) a larger validity period of the solution; b) an absence of precipitate in the slides; c) an easier visualization of the substrate; d) a larger contrast among the substrate and the bacilli.